Genetic divergence and character association studies in groundnut (Arachis hypogaea L.): Genetic divergence and character association studies in groundnut (Arachis hypogaea L.) - P M MISTRY; P K JAGTAP; R S GANVIT; A V MALVIYA (Journal of Oilseeds Research, 2020)
Correlation studies conducted in groundnut revealed that the genotypic correlations were higher than their corresponding phenotypic correlation for all the characters. Pod yield/plant was significantly and positively correlated with number of mature pods/plant, kernel yield/plant, shelling percent and days to 50% flowering whereas kernel yield/plant, number of mature pods/plant exhibited high and positive direct effects on pod yield/plant. The formation of eleven clusters in the present study suggested the presence of wide genetic diversity among the 40 genotypes studied. Test weight followed by shelling percent, kernel yield/plant, 100 kernel weight, plant height and days to 50% flowering contributed maximum towards total divergence.